THE INDICATORS OF PROFESSIONAL REFLECTION COMPETENCE OF FUTURE SPECIALISTS IN SOCIAL PEDAGOGY (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
he article deals with an issue of the specifics of future social educators' professional activity. The necessity to interact with marginal and socially unadapted groups causes certain complication of the professional activity and thus special requirements for their professional training. Professional reflection as a component of professional consciousness fulfills the function of reconciling the conscious content of professional activity, own experiences and feelings of future social educators regarding this activity.For the substantiation and development of pedagogical technology for the formation of professional reflection of future social educators in a higher educational institution, an important system of outcomes that characterized the subject of this research.
Keywords: social teacher, professional reflection, level, criterion, indicator.